O anticomunismo do jornal "A Palavra": o imaginário e suas mudanças de características (1930-1935) - MOREIRA, Danilo Sorato Oliveira (2020)
The present work intends to study Anticommunism, presented in the form of speeches, which are found in the periodical "A Palavra", paying attention to the imaginary that is propagated in this period. In addition, the innovation of the work consists in showing a diversification of this imaginary from the years 1930 to 1935. The methodology is a bibliographic analysis of the studies on Anticommunism, as well as an analysis of the journalistic sources of the Catholic periodical, A Palavra, in the period checked. The hypothesis is that in the Belenense society of the first half of the 20th century, the Catholic newspaper maintained several types of characteristics against Anti-Communism, a political idea contrary to what the editorial of this periodical was about. Thus, the final considerations are that the communist ideology was considered an enemy of the Catholic Christian faith, therefore, it was necessary to educate society through negative speeches and imaginary against the red enemy.